Using ontology to generate test cases for GUI testing. (13th February 2012) - Li, Han; Guo, He; Chen, Feng; Yang, Hongji; Yang, Yuansheng
Graphical User Interface (GUI) testing is a knowledge–intensive process. In this paper, ontology is introduced to generate user–centric GUI test cases. First, GUI and non–GUI components are captured by reverse engineering techniques. Next, relations among GUI components are analysed and a GUI ontology is constructed by representing all analysed results. Then, test case generation rules are defined and used to simplify test cases. After that, a case study is demonstrated on a general communication application, which shows that the proposed approach is technically feasible and ontology can facilitate GUI testing by utilising knowledge of GUI systems and experience of testers.